Enterocolite necrosante: uma revisão da literatura - Andréa Souza Hachem; João Cesar Lyra; Érica Cristina Scarpa; Maria Regina Bentlin (Residência Pediátrica, 2022)
OBJECTIVE: To update the topic through a literature review.